2010
DOI: 10.1007/s11002-010-9113-2
|View full text |Cite
|
Sign up to set email alerts
|

Advertising competition and industry channel structure

Abstract: Distribution channel, Competition, Advertising, Game theory,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 31 publications
(45 reference statements)
2
27
0
Order By: Relevance
“…Many researchers extended the above mentioned studies by adding other dimensions such as managerial incentives (Bhardwaj and Balasubramanian, 2005), non-price competition (Zhao et al, 2009;Liu and Tyagi, 2011;Wang et al, 2011;Zhang et al, 2012;Zhou and Cao, 2014), risk aversion (Xiao and Choi, 2009), number of players (Anderson and Bao, 2010), demand uncertainty (Cao et al, 2010). Considering managerial incentives, Bhardwaj and Balasubramanian (2005) demonstrated that an asymmetric channel structure with one integrated manufacturer and the other decentralized manufacturer arises in equilibrium.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers extended the above mentioned studies by adding other dimensions such as managerial incentives (Bhardwaj and Balasubramanian, 2005), non-price competition (Zhao et al, 2009;Liu and Tyagi, 2011;Wang et al, 2011;Zhang et al, 2012;Zhou and Cao, 2014), risk aversion (Xiao and Choi, 2009), number of players (Anderson and Bao, 2010), demand uncertainty (Cao et al, 2010). Considering managerial incentives, Bhardwaj and Balasubramanian (2005) demonstrated that an asymmetric channel structure with one integrated manufacturer and the other decentralized manufacturer arises in equilibrium.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We depart from their studies by considering endogenous channel strategies in a mixed duopoly, while they consider channel strategies of private firms. Comparisons between integrated and decentralized channels were conducted by Anderson and Bao (2010), Wang et al (2011) andZhang et al (2012), with focuses on the effect of number of players, persuasive advertising and informative advertising, respectively, but they did not study endogenous channel strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study by Wang et al. () shows that when manufacturers compete in nonprice variables such as advertising, a decentralized channel may intensify competition between manufacturers and harm the manufacturers' profits.…”
Section: Introductionmentioning
confidence: 99%
“…There has been an increase in empirical research in both economics and business fields that analyzes and quantifies the degree of competition (Eilon, 1993;Furrer and Thomas, 2000;Heiman, 2010;Liu and Nagurney, 2011;Pech and Slade, 2003;Schiavone, 2011;Sinha, 2000;Tsai and Hung, 2009;Wang et al, 2011;Xiao and Qi, 2008;Yan, Tang and Lee, 2007;Yao and Liu, 2005;Zhang, 2006). Particularly, the banking industry has fuelled a large stream of literature on competition and has been a topic of considerable interest, especially since the 80s, when significant changes in structure and competition took place in several financial markets (Lozano-Vivas and Pastor, 2010;Maudos and Pérez, 2003;Oroz and Salas, 2003).…”
Section: Introductionmentioning
confidence: 99%